Neural respiratory drive predicts clinical deterioration and safe discharge in exacerbations of COPD - Suh, Eui-Sik (Thorax, 2015)
RATIONALE: Hospitalised patients with acute exacerbation of COPD may deteriorate despite treatment, with early readmission being common. OBJECTIVES: To investigate whether neural respiratory drive, measured using second intercostal space parasternal muscle electromyography (EMG(para)), would identify worsening dyspnoea and physician-defined inpatient clinical deterioration, and predict early readmission. METHODS: Patients admitted to a single-site university hospital with exacerbation of COPD were enrolled. Spirometry, inspiratory capacity (IC), EMG(para), routine physiological parameters, modified early warning score (MEWS), modified Borg scale for dyspnoea and physician-defined episodes of deterioration were recorded daily until discharge. Readmissions at 14 and 28 days post discharge were recorded. MEASUREMENTS AND MAIN RESULTS: 120 patients were recruited (age 70±9 years, forced expiratory volume in 1 s (FEV(1)) of 30.5±11.2%). Worsening dyspnoea, defined as at least one-point increase in Borg scale, was associated with increases in EMG(para%max) and MEWS, whereas an increase in EMG(para%max) alone was associated with physician-defined inpatient clinical deterioration. Admission-to-discharge change (Δ) in the normalised value of EMG(para) (ΔEMG(para%max)) was inversely correlated with ΔFEV(1) (r=−0.38, p<0.001) and ΔIC (r=−0.44, p<0.001). ΔEMG(para%max) predicted 14-day readmission (OR 1.13, 95% 1.03 to 1.23) in the whole cohort and 28-day readmission in patients under 85 years (OR 1.09, 95% CI 1.01 to 1.18). Age (OR 1.08, 95% CI 1.03 to 1.14) and 12-month admission frequency (OR 1.29, 1.01 to 1.66), also predicted 28-day readmission in the whole cohort. CONCLUSIONS: Measurement of neural respiratory drive by EMG(para) represents a novel physiological biomarker that may be helpful in detecting inpatient clinical deterioration and identifying the risk of early readmission among patients with exacerbations of COPD. TRIAL REGISTRATION: NCT01361451.